Critical Appraisal of Communicable Diseases in the Perspective of Ayurveda - Punam Sawarkar1 , Gaurav Sawarkar2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Current situation of COVID -19 pandemic demands for search literature about in Ayurveda to generatevarious preveative & treatment modalities to over come over it. Considering this need, review regardingcommunicable disorders from available Ayurved literature was done extensively & elaborated under headsof concept of airborne communicable diseases in Ayurveda,its etiology, pathology & symptomatology withrecommended various treatment measures given in Ayurvedascripctures. It is observed that COVID -19 can becorelated with various Aoupasragic Rogas or Janapadodhwnasa Vyadhi which has similar symptomatologysimilar with Vata kapahaja Jwara. Treatment modalieties of this Jwara & some preventives measures suchas Davuavayapasharaya (spiritual practices like Homa, Havana & Yoga, Dhoopana), Yuktivyapashara(Dinachrya, Rutucharya, Vyayam, Ayurvedic drugs & herbs, Upakrama of detoxification, Rasayana Chikitsa,Dhoopana) & Satvajaya Chikitsa (Sadvrutta & Achara Rasayana) can be adopted in such condition.